The importance of autonomy in nursing home facilities - Carter, BS, Leah J.; Van Puymbroeck, PhD, CTRS, Marieke (American Journal of Recreation Therapy, 2010)
The benefits of autonomy have long been studied. This article seeks to explicate the importance of autonomy in nursing home facilities and the effect that autonomy can have on the quality of life of the residents in these long-term facilities. Autonomy is crucial in these facilities because of the impact it has on self-determination and intrinsic motivation. The benefits that come from these principles include increased participation, decreased depressive symptoms, and increased quality of life among residents. Although the importance of autonomy in nursing homes may seem elementary for many practitioners, efforts to promote autonomy are not commonly operationalized. It is important to revisit this topic because there will be an increasing number of older Americans in the years to come and it has direct implications for recreation therapy service delivery.